A comprehensive immunohistochemical examination of the distribution of the fat-burning protein irisin in biological tissues - Aydin, Suleyman; Kuloglu, Tuncay; Aydin, Suna; Kalayci, Mehmet; Yilmaz, Musa; Cakmak, Tolga; Ozercan, Ibrahim Hanifi (Elsevier Science Inc, 2014)
Irisin was first identified in skeletal muscle cells, but its precise location has not yet been demonstrated, and there is limited information about irisin protein in other human and rat tissues. The present immunohistochemical study was undertaken to screen skeletal muscle and other tissues for irisin immunoreactivity.. Irisin staining was found in the brain (neurons and neuroglia), cardiac and skeletal muscle (fibers) and skin (sebaceous glands) tissues in male rats. In both human adult and fetal skeletal muscle, the most intense immunohistochemical staining was in the perimysium and endomysium, in the peripheral nerve (epineurium) and axon and nerve sheaths spreading among the cells, in the sarcoplasma and subendomysium. Irisin was also demonstrated in the testis (seminiferous tubules, some spermatogenic cells in fetal and Leydig cells in fetal and adult testis, ductus epididymis in fetal human epididymis); pancreas (islets of Langerhans, serous acini cells, intralobular and intralobular ducts cells); liver (hepatocytes; Kupffer cells and sinusoidal endothelial cells); spleen (subcapsular region and periarterial lymphatic sheets); the stomach (gastric parietal cells, tunica muscularis cells). We conclude that the fat-burning protein irisin locally produced in peripheral and central tissues could act as a gatekeeper of metabolic energy regulation in those tissues, since this myokine converts white into brown adipose tissue, enhancing energy expenditure. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Irisin; Fetal skeletal muscle; Testis; Spleen; Brain